Perkembangan BPRS Bhakti Makmur Indah Krian: The Development of Bhakti Makmur Indah Islamic Rural Bank (BPRS), Krian - Mariyah Ulfah (Fenomena, 2007)
The Islamic rural bank (BPRS) sector in Indonesia faces the dual challenge of sustaining growth amid conventional banking dominance while ensuring Sharia compliance. This study analyzes the development and contribution of BPRS BhaktiMakmur Indah Krian in Islamic financial services. A descriptive qualitative approach was used, drawing on structured interviews with the marketing coordinator and the director, as well as bulletins and financial reports from 2002–2003. The findings show that the bank’s funding products include wadiah savings, mudarabah savings, and mudarabah deposits, while its financing products comprise murabahah, musyarakah, bay bithaman ajil, al-qard, bay al-istisna’, ijarah, and hiwalah. Murabahah accounted for 89.62% of total financing in 2002. Asset growth reached 24.14% in 2002, with profit increasing by 23.81%. The study concludes that BPRS BhaktiMakmur Indah Krian demonstrated positive financial development, yet it is recommended that the bank diversify its products and collaborate with Bank Muamalat and PNM for operational expansion. Sektor Bank Perkreditan Rakyat Syariah (BPRS) di Indonesia menghadapi tantangan ganda yaitu mempertahankan pertumbuhan di tengah dominasi bank konvensional sekaligus memastikan kepatuhan syariah. Penelitian ini bertujuan menganalisis perkembangan dan kontribusi BPRS BhaktiMakmur Indah Krian dalam jasa keuangan syariah. Metode deskriptif kualitatif digunakan dengan wawancara terstruktur kepada koordinator pemasaran dan direktur utama, serta dokumentasi buletin dan laporan keuangan tahun 2002–2003. Temuan menunjukkan bahwa produk penghimpunan dana meliputi tabungan wadiah, tabungan mudarabah, dan deposito mudarabah, sedangkan produk penyaluran dana meliputi murabahah, musyarakah, bay bithaman ajil, al-qard, bay al-istisna’, ijarah, dan hiwalah. Pembiayaan murabahah mendominasi sebesar 89,62% dari total pembiayaan tahun 2002. Pertumbuhan aset mencapai 24,14% pada 2002, dengan laba meningkat 23,81%. Penelitian menyimpulkan bahwa BPRS BhaktiMakmur Indah Krian menunjukkan perkembangan keuangan positif, namun direkomendasikan untuk diversifikasi produk dan kerja sama dengan Bank Muamalat serta PNM.